Monitoring spatial-temporal dynamics of small lakes based on SAR Sentinel-1 observations: a case study over Nui Coc Lake (Vietnam) - Pham Duc, Binh; Tong Si, Son (Vietnam Journal of Earth Sciences, 2021)
For the first time, this study estimates the variation of surface water extent of Nui Coc Lake located in Thai Nguyen province in North Vietnam at high spatial (20 m) and temporal resolution (bi-weekly). The classification methodology was developed based on the use of the Otsu threshold algorithm on the histogram of the backscatter coefficient of the SAR Sentinel-1 signal. Totally, more than 150 SAR Sentinel-1 images have been processed for the 2016-2020 period. Except for extreme drought and flood conditions, the average minimum and maximum of the lake’s surface water extent are 17 km2 (in May) and 24 km2 (in September/October), respectively, and Nui Coc Lake’s surface water was stable during the last five years. Classification results are in good agreement with the corresponding surface water extent maps derived from free-cloud Sentinel-2 images, with the occurrence map derived from the Landsat-derived Global Surface Water (GSW) product, and with in situ precipitation data. Compared to Sentinel-2, the lake’s surface water extent detected from Sentinel-1 is 4-4.5% less. The water occurrence is similar between our results and that derived from the GSW product, but Sentinel-1 data provide more details as its spatial resolution is higher than Landsat. This study clearly shows the great potential of SAR Sentinel-1 data for monitoring small lake’s water surface at low costs, especially over tropical regions.